Methylated polycyclic aromatic hydrocarbons from household coal use across the life course and risk of lung cancer in a large cohort of 42, 420 subjects in Xuanwei, China. (March 2023) - Portengen, Lützen; Downward, George; Bassig, Bryan A.; Blechter, Batel; Hu, Wei; Wong, Jason Y.Y.; Ning, Bofu; Rahman, Mohammad L.; Ji, Bu-Tian; Li, Jihua; Yang, Kaiyun; Hosgood, H. Dean; et al.
Abstract: Background: We previously showed that exposure to 5-methylchrysene (5MC) and other methylated polycyclic aromatic hydrocarbons (PAHs) best explains lung cancer risks in a case-control study among non-smoking women using smoky coal in China. Time-related factors (e.g., age at exposure) and non-linear relations were not explored. Objective: We investigated the relation between coal-derived air pollutants and lung cancer mortality using data from a large retrospective cohort. Methods: Participants were smoky (bituminous) or smokeless (anthracite) coal users from a cohort of 42, 420 subjects from four communes in XuanWei. Follow-up was from 1976 to 2011, during which 4, 827 deaths from lung-cancer occurred. Exposures were predicted for 43 different pollutants. Exposure clusters were identified using hierarchical clustering. Cox regression was used to estimate exposure–response relations for 5MC, while effect modification by age at exposure was investigated for cluster prototypes. A Bayesian penalized multi-pollutant model was fitted on a nested case-control sample, with more restricted models fitted to investigate non-linear exposure–response relations. Results: We confirmed the strong exposure–response relation for 5MC (Hazard Ratio [95% Confidence Interval] = 2.5 [2.4, 2.6] per standard-deviation (SD)). We identified four pollutant clusters, with all but two PAHs in a single cluster. Exposure to PAHs in the large cluster was associated with a higher lung cancer mortality rate (HR [95%CI] = 2.4 [2.2, 2.6] per SD), while exposure accrued before 18 years of age appeared more important than adulthood exposures. Results from the multi-pollutant model identified anthanthrene (ANT) and benzo(a)chrysene (BaC) as risk factors. 5MC remained strongly associated with lung cancer in models that included ANT and BaC and also benzo(a)pyrene (BaP). Conclusion: We confirmed the link between PAH exposures and lung cancer in smoky coal users and found exposures before age 18 to be especially important. We found some evidence for the carcinogen 5MC and non-carcinogens ANT and BaC.